Knowledge and Practice Level of Nurses Towards Geriatric Care and Its Associated Factors in Selected Public Hospitals in Wolaita Zone, Southern Ethiopia 2022 - Kebede C; Anjulo F; Meleku MM; Dessalegn LD; Geta T; Merkine M; Nigussie GB (Dove Medical Press, 2024)
Christian Kebede,1 Fekadu Anjulo,2 Melese Meleku Meleku,2 Lemma Desalegn Dessalegn,1 Temesgen Geta,3 Merid Merkine,2 Getachew Bolado Nigussie2 1Department of Pediatrics and Child Health Nursing, School of Nursing, College of Health Science and Medicine, Wolaita Sodo University, Wolaita, Ethiopia; 2Department of Adult Health Nursing, School of Nursing, College of Health Science and Medicine, Wolaita Sodo University, Wolaita, Ethiopia; 3Department of Maternity and Reproductive Health Nursing, School of Nursing, College of Health Science and Medicine, Wolaita Sodo University, Wolaita, EthiopiaCorrespondence: Christian Kebede, Department of Pediatrics and Child Health Nursing, School of Nursing, College of Health Science and Medicine, Wolaita Sodo University, P.O. Box: 138, Wolaita, Ethiopia, Tel +251924741458, Email kebedechristian@gmail.comIntroduction: Geriatric care expertise encompasses the theoretical and practical understanding of providing care for older adults. This knowledge is acquired through the education and experience of healthcare practitioners. Recognizing the knowledge and practice level in this field is highly critical for improving its quality. Nevertheless, there is a dearth of research concerning the knowledge and practice levels of nurses involved in geriatric care in Ethiopia.Objective: To determine the knowledge and practice level of nurses towards geriatric care and its associated factors in selected public hospitals in Wolaita Zone, Southern Ethiopia, in 2022.Methods: A cross-sectional study was carried out in selected public hospitals, focusing on nurses working in adult nursing facilities. An interviewer-administered questionnaire was implemented to evaluate the knowledge and practice level of nurses in geriatric care. Based on the collective responses of the participants, the levels were categorized as either good or poor. A binary logistic regression model was utilized to evaluate the effects of independent variables on the outcome variables.Results: Overall, 57.2% and 45.3% of the study participants had good knowledge and practice levels in geriatric care, respectively. Educational level, years of experience, and participation in geriatric nursing education were significantly associated with nurses' knowledge of geriatric care. Nurses' knowledge level towards geriatric care and having training on geriatric care were significantly associated with nurses' level of practice of geriatric care.Conclusion: Considering the insufficient knowledge and practice of geriatric care among nurses, it is imperative for hospital administrators to offer frequent training opportunities and integrate essential geriatric care education into the nursing curriculum.Keywords: aging care, caregivers, factors, nursing care